2020
DOI: 10.1371/journal.ppat.1008589
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing analysis of a “hit and run” cell and animal model of KSHV tumorigenesis

Abstract: Kaposi's sarcoma (KS), is an AIDS-associated neoplasm caused by the KS herpesvirus (KSHV/ HHV-8). KSHV-induced sarcomagenesis is the consequence of oncogenic viral gene expression as well as host genetic and epigenetic alterations. Although KSHV is found in all KS-lesions, the percentage of KSHV-infected (LANA+) spindle-cells of the lesion is variable, suggesting the existence of KS-spindle cells that have lost KSHV and proliferate autonomously or via paracrine mechanisms. A mouse model of KSHVBac36-driven tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 55 publications
(136 reference statements)
4
29
0
Order By: Relevance
“…Unsupervised analysis of 14 samples based on miRNAs expression profiles shows how they cluster together in an unsupervised way according to their predefined features ( Figure 4A). Interestingly, the samples cluster in the same pattern as when the analysis was made for lncRNAs ( Figure 1B) and also for all host genes in our previous study [Naipauer et al, 2020]. The distance among groups is reflexed in the number of DE miRNAs ( Figure 4B; S4 Table).…”
Section: -Kshv-dependent In Vitro To In Vivo Transition Is Defined Bsupporting
confidence: 70%
See 3 more Smart Citations
“…Unsupervised analysis of 14 samples based on miRNAs expression profiles shows how they cluster together in an unsupervised way according to their predefined features ( Figure 4A). Interestingly, the samples cluster in the same pattern as when the analysis was made for lncRNAs ( Figure 1B) and also for all host genes in our previous study [Naipauer et al, 2020]. The distance among groups is reflexed in the number of DE miRNAs ( Figure 4B; S4 Table).…”
Section: -Kshv-dependent In Vitro To In Vivo Transition Is Defined Bsupporting
confidence: 70%
“…To identify changes in host lncRNAs expression profile we analyzed the number of differentially expressed (DE; FC>1.5, pvalue <0.05) lncRNAs in key biological comparisons that were detected by RNA-sequencing analysis of: two KSHV (+) cells, two KSHV (-) cells, six KSHV (+) tumors, two KSHV (-) tumor cells and three KSHV (-) tumors (S1 Table). This mouse model allows for unique experimental comparisons in the same cell and KS-like mouse tumor types: 1) KSHV (-) cells versus KSHV (+) cells can be used to study KSHV mediated effects in vitro, 2) KSHV (-) tumors versus KSHV (+) tumors can be used to dissect the role of ncRNAs in tumorigenesis by comparing tumors driven by KSHV versus tumors driven by host mutations, 3) KSHV (+) cells grown in vitro and in tumors can be used to study in vitro versus in vivo variations induced by micro-environmental cues, and 4) KSHV (-) tumor cells versus KSHV (-) tumors can be used to study in vitro versus in vivo variations in the absence of KSHV [Naipauer et al, 2020]. We first analyzed lncRNAs expression in these comparisons and found that the highest number of DE lncRNAs was observed in KSHV (+) tumors in both comparisons versus KSHV (-) tumors and versus KSHV (+) cells ( Figure 1D; S1 Table).…”
Section: -Genome-wide Analysis Of Non-coding Rnas In a Cell And Animmentioning
confidence: 99%
See 2 more Smart Citations
“…There are recent postulations for a ‘hit-and-run’ hypothesis suggesting that the accumulation of other genomic mutations could supersede the tumor’s dependence on the viral oncogenes resulting in a virus-independent tumor (Reviewed in [ 130 ]). This virus-independence has been observed with the spontaneous loss of EBV episomes in a Burkitt’s lymphoma (BL) cell line [ 131 ], or KSHV transformed cell lines that are episome negative but still tumorigenic in mice [ 132 ], and even in instances of HPV-related cancers, often considered a clear example of oncogenic addiction, known HPV18 transformed cell lines can lack HPV DNA [ 133 ]. Future studies should focus on clarifying the context and extent to which these cancers are dependent on viral elements, as this insight would allow for the cognizant application of nucleases in the treatment of virus-associated cancers.…”
Section: ‘Hit-and-run’ Virally Driven Cancersmentioning
confidence: 99%